2010 IEEE International Conference on Intelligent Systems and Knowledge Engineering 2010
DOI: 10.1109/iske.2010.5680812
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent fuzzy controller of a quadrotor

Abstract: The aim of this work is to describe an intelligent system based on fuzzy logic that is developed to control a quadrotor. A quadrotor is a helicopter with four rotors, that make the vehicle more stable but more complex to model and to control. The quadrotor has been used as a testing platform in the last years for various universities and research centres. A quadrotor has six degrees of freedom, three of them regarding the position: height, horizontal and vertical motions; and the other three are related to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(75 citation statements)
references
References 11 publications
0
71
0
4
Order By: Relevance
“…Logika ini menggunakan pendekatan alamiah layaknya manusia dalam menentukan suatu keputusan [7]. Logika fuzzy dapat digunakan untuk mengoptimalkan respon dari sistem kendali PID dengan merujuk pada karakteristik konstanta Kp, Ki, dan Kd [8].…”
Section: Analisis Sistemunclassified
“…Logika ini menggunakan pendekatan alamiah layaknya manusia dalam menentukan suatu keputusan [7]. Logika fuzzy dapat digunakan untuk mengoptimalkan respon dari sistem kendali PID dengan merujuk pada karakteristik konstanta Kp, Ki, dan Kd [8].…”
Section: Analisis Sistemunclassified
“…The result of the experiment showed that the fuzzy can be used to control a motor on quadrotor. The other researchers named Santos et al [8] have applied fuzzy logic control with mamdani method to control the x, y, and z positions in quadrotor. This algorithm is used and modified for membership output members with 5 members to control the positions of x, y, and z in quadrotor in an undisturbanced environment.…”
Section: Hovering Control Of Quadrotor Based On Fuzzy Logic (Nia Mahamentioning
confidence: 99%
“…Coza and Macnab [7] provides a new method to design the adaptive-fuzzy controller to achieve stabilization of a quadrotor helicopter in the presence of sinusoidal wind disturbance. Santos et al [41] also implemented a fuzzy controller to control the quadrotor. And [19] proved its FLC can obtain the expected performances in the UAV control and navigation tasks.…”
Section: Related Workmentioning
confidence: 99%